2007
DOI: 10.1089/scd.2007.0006
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenesis of Chemotherapeutic Drug-Resistant Cancer Stem-Like Cells in Brain Glioma

Abstract: Glioblastoma multiforme (GBM) is the most frequently occurring brain cancer. Although the existence of cancer stem cells (CSCs) in GBM has been established, there is little evidence to explain the link between CSCs and chemoresistance. In this study, we developed a dissociated cell system of human GBM cells, A172 and established GBM2 cells, that have shown resistance to 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU). After exposure to a lethal dose of BCNU, the small population of GBM cancer cells survived and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 26 publications
4
143
0
Order By: Relevance
“…5 Although tumorigenicity may be not confined entirely to the CD133-positive cell fraction of glioblastoma, [6][7][8][9] growing data demonstrate that CD133 expression is related to an adverse prognosis [10][11][12][13][14] and that the CD133-expressing glioblastoma cells contribute to radiochemoresistance and tumor aggressiveness. [15][16][17][18][19] For example, Liu and colleagues demonstrated a positive selection for CD133-positive tumor cells in patients with glioblastoma after chemotherapy. 15 The resistance of CD133-positive glioblastoma cells to cytotoxic drugs was related to high levels of drug transporter and inhibitor of apoptosis proteins and to enhanced methyl guanine-DNA methyl transferase (MGMT)-mediated DNA repair pathways.…”
mentioning
confidence: 99%
“…5 Although tumorigenicity may be not confined entirely to the CD133-positive cell fraction of glioblastoma, [6][7][8][9] growing data demonstrate that CD133 expression is related to an adverse prognosis [10][11][12][13][14] and that the CD133-expressing glioblastoma cells contribute to radiochemoresistance and tumor aggressiveness. [15][16][17][18][19] For example, Liu and colleagues demonstrated a positive selection for CD133-positive tumor cells in patients with glioblastoma after chemotherapy. 15 The resistance of CD133-positive glioblastoma cells to cytotoxic drugs was related to high levels of drug transporter and inhibitor of apoptosis proteins and to enhanced methyl guanine-DNA methyl transferase (MGMT)-mediated DNA repair pathways.…”
mentioning
confidence: 99%
“…Although 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) is a commonly used chemotherapy for patients with glioblastoma multiforme, a small population of glioma cells containing BTSCs are resistant to BCNU (Kang and Kang 2007). These resistant glioma BTSCs have been reported to over-express a number of ion channel genes related to drug efflux (Kang and Kang 2007), especially chloride intracellular channel 1 .…”
Section: Chemotherapymentioning
confidence: 99%
“…These resistant glioma BTSCs have been reported to over-express a number of ion channel genes related to drug efflux (Kang and Kang 2007), especially chloride intracellular channel 1 . Combined treatment with the chloride channel blocker 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (DIDS) and BCNU increased sensitivity to BCNU ex vivo and enhanced apoptosis in BCNU-resistant BTSCs in vitro .…”
Section: Chemotherapymentioning
confidence: 99%
“…BCNU is a commonly used chemotherapeutic agent for glioblastoma therapy, but in primary glioma tumor mass, there is a subpopulation of BCNU-resistant glioma cells, which are stem-like cells, because the authors found that this subpopulations expressed CD133, CD117, CD90, CD71, and CD45 cell-surface markers, and had the capacity for multipotency (Kang & Kang, 2007). In the dissociated BCNU-resistant glioma stem cells, there was a high expression of several types of ionic channels, the chloride intracellular channels 1 (CLIC1) was one of these high expression channels.…”
Section: Ionic Channels In Brain Tumor Stem Cellsmentioning
confidence: 99%